Freud and (the absence of) Pandora - Fernandez de Souza, Pedro (Revista Archai, 2022)
The Freudian theory of femininity is the object of several studies. We intend to make a contribution to this debate, but instead of approaching the Freudian texts in which woman appears explicitly, we aimed to read a specific Freudian text in which she appears not, although she should do so. It is the 1932 text Zur Gewinnung des Feuers, in which the father of psychoanalysis interprets the myth of Prometheus. The fact is that, in Hesiod, the figure of the first woman (Pandora) is central, and one cannot comprehend the myth in its totality without her. In Freud’s version, Pandora does not exist - she is not taken in consideration and is not even mentioned. Therefore, instead of the myth of Prometheus and Pandora, we have in Freud the myth of Prometheus - and that does not come without consequences. Thus, Freud’s masculine writing would lie not only where he expatiates on women, but also where she does not even appear.